The role of the formation of buffer V2O5 inclusions in the composition of composite ZrO2 – Al2O3 ceramics on the change in strength characteristics - G.B. Сейтмағанбет; M.V. Здоровец; A.V. Труханов (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
The paper presents the assessment results of the effect of addition of V2O5 dopant to the composition of composite ZrO2 – Al2O3 ceramics and the formation of buffer inclusions on resistance to external mechanical influences and enhancement of resistance to cracking under mechanical loads. During the studies conducted, it was established that the addition of the V2O5 dopant to the composition of ceramics with a concentration above 0.1 M leads to the formation of buffer inclusions in the intergranular space formed by ZrO2 grains and the Al2O3 matrix, while the formation of buffer inclusions is due to the low melting point of V2O5, resulting in the melting of vanadium oxide during sintering and subsequent vitrification and crystallization during cooling in the intergranular space. During assessment of the strength characteristics, in particular hardness, crack resistance and compressive strength, it was found that at low dopant concentrations, strengthening is caused by structural changes associated with size effects, which are expressed in the growth and coarsening of ZrO2 grains in the Al2O3 matrix. At concentrations above 0.1 M, the growth in resistance to external influences is due to the formation of buffer inclusions, the filling of the intergranular space with which leads to the inhibition of crack formation processes and an increase in resistance to mechanical loads.